Exploring the Cultural Expressions in Ese'eja Adolescents of the Native Community of Infierno, Peru - Sillo-Sosa, Jaffet (2023)
Objective: To determine the level of knowledge of Este’ja cultural expressions in the students of the Shajao Educational Institution of the Native Community of Infierno, Peru. Theoretical framework: This research is based on a theoretical framework that highlights the importance of understanding and preserving the cultural expressions of indigenous communities in the context of adolescence. Method: A quantitative approach and a non-experimental design were used to analyze the influence of the characteristics and values detected in a questionnaire of 30 questions. This questionnaire was applied to an objective sample of 46 high school students. Results and conclusions: The results indicated that the level of knowledge of cultural expressions that varies from an average knowledge to a high one. Additionally, it was discovered that Ese'eja handicrafts are frequently practiced for economic purposes, while traditions are maintained when students participate in them and consider them useful for their lives. Finally, it was observed that Ese'eja original language is frequently used in family environments. Research implication: This research is expected to contribute to the preservation and promotion of Ese'eja culture, highlighting the cultural expressions of adolescents. In addition, this can have a positive impact on the conservation of the cultural heritage of the community. Originality/Value: To promote greater understanding and appreciation of cultural diversity between urban and non-indigenous populations in Peru and other places. This could promote tolerance and respect for indigenous communities.